The low-wage sector in Germany is larger than previously assumed - Markus M. Grabka; Carsten Schröder (DIW Weekly Report, 2019)
The total number of dependent employees in Germany has increased by more than four million since the financial crisis. Part of this growth took place in the low-wage sector. Analyses based on data from the Socio-Economic Panel, which in 2017 for the first time include detailed information on secondary employment, show that there were around nine million low-wage employment contracts in Germany that year, around one quarter of all contracts. Women, young adults and employees in Eastern Germany are particularly likely to receive low wages. The legal minimum wage introduced in 2015 is below the low-wage threshold, and thus did not decrease the proportion of low-wage employees, although wages at the bottom-end of the distribution did markedly increase. Wage mobility has hardly changed since the mid-1990s: almost two thirds of employees in the lowest wage category were still there three years later. In order to curtail the low-wage sector, a better and broader qualification of workers, as well as a more proactive wage policy are called for. A reform of the mini-job rules would also be helpful.
Keywords: D31; I31; I32; 330; wages; inequality; working-poor; mobility; SOEP